The Tradition of the Twins Mayang in Javanese Tribe Community Wedding in Sukamaju Village, Banggai District in the Perspective of Islamic Law - Malik Firdaus, Abdul; S. Thahir, Lukman; Akbar, Muhammad (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2023)
The twin mayang tradition is still being maintained and believed to be a way to bring goodness to the bride and groom and their families who carry out the wedding ceremony. The purpose of this research is to find out the form, process, value and philosophical meaning of the twin manyang tradition at Javanese weddings in the village of Suka Maju and its review in Islamic law. This research uses descriptive qualitative research with a cultural anthropological approach. This approach explains that a religion is not studied or researched by itself but is examined by linking it with other aspects. So that this research is not only to be able to know the law and its implementation but also to be able to understand the value and philosophical meaning in it so that it can benefit people's lives. Data was collected through observation and structured interviews and some supporting data in the form of files and other documents. The results of this study indicate that the twin mayang tradition in Javanese weddings is a tradition in which there are values, functions and benefits for the wedding couple. Twin mayang has a philosophical meaning and good messages and advice in running a household life, so that these values become the basis for continuing to preserve this tradition. In a review of Islamic law, the twin mayang tradition has Islamic values and principles. Islamic principles include the principles of monotheism, freedom, justice, mutual help and expediency. So thus the twin mayang tradition is a tradition that contains Islamic principles and is permissible as long as it does not conflict with Islamic law.